On race and ethnicity during a global pandemic: An ‘imperfect mosaic’ of maternal and child health services in ethnically-diverse South London, United Kingdom - Silverio, Sergio A.; De Backer, Kaat; Dasgupta, Tisha; Torres, Ofelia; Easter, Abigail; Khazaezadeh, Nina; Rajasingam, Daghni; Wolfe, Ingrid; Sandall, Jane; Magee, Laura A. (EClinicalMedicine, 2022)
The SARS-CoV-2 pandemic has brought racial and ethnic inequity into sharp focus, as Black, Asian, and Minority Ethnic people were reported to have greater clinical vulnerability. During the pandemic, priority was given to ongoing, reconfigured maternity and children's healthcare. This study aimed to understand the intersection between race and ethnicity, and healthcare provision amongst maternity and children's healthcare professionals, during the SARS-CoV-2 pandemic. A qualitative study consisting of semi-structured interviews (N = 53) was undertaken with maternity (n = 29; August-November 2020) and children's (n = 24; June-July 2021) healthcare professionals from an NHS Trust in ethnically-diverse South London, UK. Data pertinent to ethnicity and race were subject to Grounded Theory Analysis, whereby data was subjected to iterative coding and interpretive analysis. Using this methodology, data are compared between transcripts to generate lower and higher order codes, before super-categories are formed, which are finally worked into themes. The inter-relationship between these themes is interpreted as a final theory. Grounded Theory Analysis led to the theory: An ‘Imperfect Mosaic’, comprising four themes: (1) ‘A System Set in Plaster’; (2) ‘The Marginalised Majority’; (3) ‘Self-Discharging Responsibility for Change-Making’; and (4) ‘Slow Progress, Not No Progress’. The NHS was observed to be brittle, lacking plasticity to deliver change at pace. Overt racism based on skin colour has been replaced by micro-aggressions between in-groups and out-groups, defined not just by ethnicity, but by other social determinants. Contemporaneously, responsibility for health, wellbeing, and psychological safety in the workplace is discharged to, and accepted by, the individual. Our findings suggest three practicable solutions: (1) Representation of marginalised groups at all NHS levels; (2) Engagement in cultural humility which extends to other social factors; and (3) Collective action at system and individual levels, including prioritising equity over simplistic notions of equality. This service evaluation was supported by the King's College London King's Together Rapid COVID-19 Call, successfully awarded to Laura A. Magee, Sergio A. Silverio, Abigail Easter, & colleagues (reference:- 204823/Z/16/Z), as part of a rapid response call for research proposals. The King's Together Fund is a Wellcome Trust funded initiative.